Usefulness of the 6-minute walk test vs cardiopulmonary exercise test for exercise prescription in coronary artery disease patients going into a phase III cardiac rehabilitation program. (11th May 2022) - Sevegnani, C; Gameiro, J; Borges, M; Pires, ML; Nunes, A; Abreu, A; Pinto, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Determining the intensity of exercise is a very important component to obtain the dose-benefits associated with exercise, while maitaining the safaty of the patient with coronary artery disease (CAD) in a cardiovascular rehabilitation (CR) programme. The cardiopulmonary exercise test (CPET) is the gols standard for exercise prescription according to the intend intensisty of aerobic workout. However, its availability is not a reality in many CR centres. The 6-minute walk test (6MWT) is a valid and widely used method because it is low-cost and simple to apply. Nevertheless, it is still unknown the corresponding intensity reached on a 6MWT compared to the one reached on a CPET in already physically active patients with CAD starting a CR phase III programme. Purpose: To use the peak heart rate (HR) of the 6MWT as a method to prescribe the intensity of aerobic exercise in CAD patients starting a phase III CR programme and to compare it with the ventilatory threshold (VT) of the CPET. Methods: In this retrospective study, a cohort of patients with CAD enrolled in a phase III CR programme. At the beginning of the programme, all patients performed a 6MWT and a CPET in the same week with at least 48-hour difference. The HR on the 6MWT was recorded continuously using a HR polar (H10 Polar) and on CPET using a twelve-lead ECG. Other parameters were assessed such as objective physical activity (accelerometer) and body composition. Results: Eighty patients (87.5% males, 60.8 ± 9.4 years old) with CAD were included in this study. Patients were, on average, physically active (361 ± 182 minutes/week of moderate to vigorous physical activity) and overweight (body mass index: 27.7 ± 3.5 kg/m2). The VO2 peak reached on the CPET was 20.3 ± 5.4 ml/kg/min and the percentage of predicted maximum HR was 78.3 ± 11.4 %. The first and second VT corresponded to 75.6 ± 7.8% and 91.2 ± 4.5% of the peak HR obtained with CPET, respectively. The 6MWT HR peak was 113 ± 16 bpm (90.0 ± 13.0 HR peak CPET) and did not differ from the HR of the second VT with a mean value of 115 ± 16 bpm (91.2 ± 4.5% HR peak CPET), p>0.05. Although, the 6MWT HR peak was significantly higher than the HR oh the first VT (95 ± 14 bpm, p<0.001). In a subgroup analysis, the patients who, during the 6MWT, reached more the 90% of the HR peak CPET (n=35, 44% oof the sample) were the ones with lower functional capacity (VO2 peak: 18.4 ± 5.4 ml/kg/min vs 21.7 ± 5.0 ml/kg/min, p=0.006) and higher age (64.4 ± 8.7 years old vs 60.8 ± 9.4 years old, p=0.002). Conclusion(s): In the absence of a CPET, the use of a 6MWT HR peak in physically active patients with CAD starting a phase III CR programme has shown to be an efficient method to prescribe moderate to vigorous exercise intensity, corresponding to the second VT. Higher intensities on the 6MWT might be reached in active elderly patients with reduced functional capacity.